School vision and mission as reflected in the elementary English curriculum - Vergara, Concepcion Ramos (2005)
The data collections were both qualitative and quantitative. Results showed that the school's vision and mission are clearly stated, well-defined, congruent and properly aligned with the departmental and instructional goals of English. Learning opportunities were creatively planned, relevant, coherent, appropriate, feasible, varied and have optimal values. The core values that were deliberately chosen made the school distinct and unique from other schools, as well as the defined related values and Standards of Learning or learning indicators were deemed indispensable in curriculum planning and development.
"March 2005."
Thesis (M.A. Education : Curriculum and Instruction)--University of the Philippines Diliman.
Keywords: Curriculum evaluation -- Philippines -- Quezon City; English language -- Study and teaching (Elementary) -- Philippines -- Quezon City; Catholic schools -- Curricula -- Philippines -- Quezon City